1639 Va. Acts 226, Act 10 - (:unkn) unknown (My University, 1639)
All persons except negroes to be provided with arms and ammunition or be fined at pleasure of the Governor and Council.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES; REQUIRED POSSESSION